2008
DOI: 10.5194/bg-5-1145-2008
|View full text |Cite
|
Sign up to set email alerts
|

Microzooplankton grazing and phytoplankton growth in marine mesocosms with increased CO<sub>2</sub> levels

Abstract: Abstract. Microzooplankton grazing and algae growth responses to increasing pCO 2 levels (350, 700 and 1050 µatm) were investigated in nitrate and phosphate fertilized mesocosms during the PeECE III experiment 2005. Grazing and growth rates were estimated by the dilution technique combined with taxon specific HPLC pigment analysis. Microzooplankton composition was determined by light microscopy. Despite a range of up to 3 times the present CO 2 levels, there were no clear differences in any measured parameter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 42 publications
(26 reference statements)
5
48
5
Order By: Relevance
“…The ecosystem composition, bacterial and phytoplankton abundances and productivity, grazing rates and total grazer abundance and reproduction were not significantly affected by CO 2 induced effects Riebesell et al, 2008;Egge et al, 2007;Paulino et al, 2007;Larsen et al, 2007;Suffrian et al, 2008;Carotenuto et al, 2007). This finding suggests that the system under study was surprisingly resilient to abrupt and large pH changes.…”
Section: Discussionsupporting
confidence: 51%
“…The ecosystem composition, bacterial and phytoplankton abundances and productivity, grazing rates and total grazer abundance and reproduction were not significantly affected by CO 2 induced effects Riebesell et al, 2008;Egge et al, 2007;Paulino et al, 2007;Larsen et al, 2007;Suffrian et al, 2008;Carotenuto et al, 2007). This finding suggests that the system under study was surprisingly resilient to abrupt and large pH changes.…”
Section: Discussionsupporting
confidence: 51%
“…Acidification has been shown to reduce viral production in mixed blooms dominated by diatoms and E. huxleyi (Larsen et al, 2008), for example, although little effect was found on microzooplankton standing stock or grazing activity (Suffrian et al, 2008). M. pusilla populations can collapse rapidly due to viral lysis and microzooplankton grazing (Evans et al, 2003), and it is possible that the shifts in picoeukaryote community composition we observed in the present study may have been due to reduced predation of Micromonas in the acidified enclosures.…”
Section: Diversity Of Form I Rbcl Sequencescontrasting
confidence: 36%
“…in food availability, phytoplankton community structure, size classes and stoichiometry (Suffrian et al, 2008;Feng et al, 2009;Rossoll et al, 2012). On the other hand MZP are known for a direct pH sensitivity (Hinga, 2002;, and a drop in seawater pH as a result of increasing pCO 2 could directly affect the physiology of both autotrophic and heterotrophic protists by changing, e.g.…”
Section: N Aberle Et Al: Tolerance Of Microzooplankton To Ocean Acimentioning
confidence: 99%
“…Only some small, chloroplast-bearing dinoflagellates were considered as predominantly autotrophic and included into the phytoplankton. MZP were identified to the lowest possible taxonomic level (species or genus level) according to Kahl (1932), Foissner et al (1995), Strüder-Kypke et al (2002), Tomas (1996) and Scott (2005). For biovolume calculations geometric proxies were used according to Hillebrand et al (1999), and carbon biomass was calculated using the conversion factors given in Putt and Stoecker (1989).…”
Section: Microzooplankton Sampling and Identificationmentioning
confidence: 99%
See 1 more Smart Citation